(untitled) (Journal of Comparative & International Higher Education, 2024)
To fully understand how socio-economic backgrounds shape the university experiences of international students, cross-national measures of social class are needed. This paper offers a contribution to understandings of social class cross-nationally through semi-structured interviews with sixteen international students. It argues that an emphasis on international students’ emotional commentaries may offer important insights into subjective understandings of social class that may not otherwise be identified. Participants were able to locate themselves within the societal structure of their own country with conceptualizations of “top,” “middle,” and “bottom” related to income differentials. Emotional injuries relating to a sense of “working-class-ness” were evident in international students’ narratives with hope, fear, and shame prevalent in these accounts. The findings from this study can inform tailored international student support provision, contribute to a more nuanced understanding of the university experience of this group, and challenge the narrative that all international students are “privileged”.